Main Lines of Regional Economic Development in a Globalising Economy - Erdélyi, Tea; Pirisi, Károly; Molnár, Attila (Acta Carolus Robertus, 2025)
The socio-economic changes of the last decades have shifted development opportunities towards qualitative development. The need for intensive development and innovation has required the development of a new type of institutional framework, a challenge that most Western European countries have been trying to meet since the 1970s and 1980s. The theoretical part of this paper presents these pacts and their afterlives. Stakeholder-based pacts enable economic development based on local conditions by providing the right quantity and quality of labour, taking into account social interests at the regional level.The study focuses the structures and processes that can make a development pact effective. Aim of the authors is to identify these characteristics and to make suggestions that could be useful in restructuring domestic employment pact system. To this end, the paper compares the Austrian employment pacts of the early 2000s and the Hungarian employment pacts of the 2000s.
Keywords: intensive economic development; organisational structure; organisational culture; organisational communication